PENYELESAIAN SENGKETA PERDATA DI PENGADILAN NEGERI DALAM KAITANNYA DENGAN TRANSAKSI YANG MENGGUNAKAN INTERNET - I Made Duwi Putra; Anak Agung Ngurah Yusa Darmadi (Kertha Negara : Journal Ilmu Hukum, 2014)
The growth of technological Progress make the change of pattern in the socializehuman life, and it can conduct the economic activity in the local scale, regional and alsoglobal. In the individual assocciation by using internet technology will take the relationpattern between individual which is unlike what that happened in the real. By the existenceof internet, contractual terms between subject of law and each other without meeting (faceto face), even it is enabled for subject of law not to recognizing each other.During thepeople conducting activity in the illusory world, especially in the private law, likecommerce, agreement and also banking activity, it is enabled to take a problems such asperformed in the conventional private relationship. If the internet consumers in the privateactivity feel their private rights are impinged and they are wish to claim their rights, sothere is civil dispute. The relationship between the individual in the transaction usinginternet not arrange peculiarly yet in law. But judge have to find the law and also createthe law if he confronted with a dispute in the transaction using internet.